2017
DOI: 10.1017/sjp.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Adaptation of the Morningness-Eveningness-Stability-Scale improved (MESSi)

Abstract: The aim of the present study was to conduct the preliminary adaptation of the Morningness-Eveningness-Stability-Scale improved (MESSi) to Spanish population, testing its factor structure and construct validity. Participants were 261 adults (65% women; M = 31.4, SD = 12.01) who filled out measures of Morningness-Eveningness (MESSi and CSM), sleep habits, personality traits, positive and negative affect, and subjective level of alertness during the day. Psychometric results supported a three factorial model with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Higher MA or EV scores represent higher morning and evening orientation, respectively, while higher DI values indicate higher daytime fluctuations. MESSi's factorial invariance, structure, and reliability have already been confirmed repeatedly in different languages [18,[20][21][22][23]. In addition, actigraphy data corroborated the validity of the MESSi [24].…”
Section: Chronotypesupporting
confidence: 56%
“…Higher MA or EV scores represent higher morning and evening orientation, respectively, while higher DI values indicate higher daytime fluctuations. MESSi's factorial invariance, structure, and reliability have already been confirmed repeatedly in different languages [18,[20][21][22][23]. In addition, actigraphy data corroborated the validity of the MESSi [24].…”
Section: Chronotypesupporting
confidence: 56%
“…Specifically, Morning Affect correlated positively and Eveningness correlated negatively with the CSM (Randler et al, 2016a) and with the rMEQ (Díaz-Morales and Randler, 2017; Faßl et al, 2018). Regarding Distinctness, the correlation between its scores and the CSM and the rMEQ was negative but lower than with the other two subscales (Randler et al, 2016a; Díaz-Morales and Randler, 2017). Moreover, in the study by Faßl et al (2018), no correlations were found between Distinctness and the other subscales.…”
Section: Introductionmentioning
confidence: 96%
“…The MESSi has been submitted to several validation studies, namely in Germany, Spain, Iran, Portugal, and Slovenia (Randler et al, 2016a; Díaz-Morales and Randler, 2017; Diaz-Morales et al, 2017; Rahafar et al, 2017; Rodrigues et al, 2018; Tomažič and Randler, 2019). In short, all studies have replicated the three-factor internal structure (i.e., Morning Affect, Eveningness, and Distinctness) via exploratory (Randler et al, 2016a) or confirmatory factor analyses (Díaz-Morales and Randler, 2017; Diaz-Morales et al, 2017; Rahafar et al, 2017; Rodrigues et al, 2018). However, the factor structure has not been challenged by comparing a one-, two- or three-factor structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations